Education about Waste Management and Community Empowerment through Waste Banks - Irmayani, Irmayani; Ginting, Rosita; Bangun, Sri Melda; Parinduri, Anggi Isnani; Samura, Jul Asdar; Darma, Surya (JURNAL PENGMAS KESTRA (JPK), 2024)
Background: Ineffective waste management has become a serious problem in many areas, both urban and rural. Accumulating rubbish can pollute the environment, cause various diseases and damage the ecosystem. One effective approach to overcome this problem is through providing education about management and the establishment of community-based waste banks. Objective: Community service activities have the aim of providing education and empowering the community in waste management through the formation and management of waste banks. Method: This community service activity goes through several stages, namely identification and analysis of needs; discussions with village officials, community leaders and stakeholders; preparation of activity programs; material determination; preparation of facilities and infrastructure; providing education about waste management and socializing waste banks; establishing a waste bank management structure as well as monitoring and evaluation. Results: The result of this community service activity is an increase in community understanding about good waste management by 80% and the formation of 1 waste bank unit that can be utilized by the community as well as the formation of a management structure for waste bank management. It is hoped that by establishing a waste bank unit, the community will have access to a more structured waste management system, while also gaining economic benefits from inorganic waste management.